Perspectives on the Formal Authority between Project Managers and Change Managers. Issue 5 (October 2014) - Pollack, Julien; Algeo, Chivonne
Project management and change management both contribute to the management and delivery of changes to organizations; however, they are based on distinct bodies of knowledge, and practitioners of these disciplines have disparate views on how change should be managed. There is a lack of consensus about how these disciplines should work together to deliver organizational change projects, which may result in conflict. This research delves into practitioners' perspectives on formal authority, the reporting relationship between these disciplines, and also reveals the fundamental differences in how practitioners of these disciplines view the practice of organizational change.